2018
DOI: 10.1016/j.meegid.2018.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of Plasmodium falciparum histidine-rich protein-2 (pfhrp2) and pfhrp3 gene deletions using whole-genome sequencing data and meta-analysis

Abstract: Many rapid diagnostic tests (RDT) used on suspected malaria cases are based on the detection of the protein encoded by the Plasmodium falciparum histidine-rich protein-2 (pfhrp2) gene, which shares a high sequence homology with pfhrp3 in the 3D7 reference genome. Parasite isolates showing pfhrp2 and pfhrp3 gene deletions have been emerging over the years, but a comprehensive genetic analysis of these variants is still lacking. With this purpose, genomic data from experimental P. falciparum genetic crosses betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 49 publications
4
59
0
Order By: Relevance
“…Parasites with gene deletions of hrp2 and/or hrp3 have emerged as an important cause of RDT failure in a number of locations [75][76][77][78][79] . It is difficult to devise a simple genetic assay to monitor for risk of RDT failure because hrp2 and hrp3 deletions comprise a diverse mixture of large structural variations with multiple independent origins, and both genes are located in subtelomeric regions of the genome with very high levels of natural variation 29,[80][81][82][83] . In the absence of a well-validated algorithmic method, we visually inspected sequence read coverage and identified samples with clear evidence of large structural variants that disrupted or deleted the hrp2 and hrp3 genes.…”
Section: Hrp2/3 Deletions That Affect Rapid Diagnostic Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasites with gene deletions of hrp2 and/or hrp3 have emerged as an important cause of RDT failure in a number of locations [75][76][77][78][79] . It is difficult to devise a simple genetic assay to monitor for risk of RDT failure because hrp2 and hrp3 deletions comprise a diverse mixture of large structural variations with multiple independent origins, and both genes are located in subtelomeric regions of the genome with very high levels of natural variation 29,[80][81][82][83] . In the absence of a well-validated algorithmic method, we visually inspected sequence read coverage and identified samples with clear evidence of large structural variants that disrupted or deleted the hrp2 and hrp3 genes.…”
Section: Hrp2/3 Deletions That Affect Rapid Diagnostic Testsmentioning
confidence: 99%
“…These data have become a key resource for the epidemiology and population genetics of antimalarial drug resistance [9][10][11][12][13][14][15][16][17][18][19][20][21][22] and an important platform for the discovery of new genetic markers and mechanisms of resistance through genome-wide association studies [23][24][25][26][27] and combined genome-transcriptome analysis. 28 The data have also been used to study gene deletions that cause failure of rapid diagnostic tests 29 ; to characterise genetic variation in malaria vaccine antigens 30,31 ; to screen for new vaccine candidates 32 ; to investigate specific host-parasite interactions 33,34 ; and to describe the evolutionary adaptation and diversification of local parasite populations. 7,9,12,[35][36][37][38][39][40] The Pf Community Project data also provide an important resource for developing and testing new analytical and computational methods.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have stated that the deletion of those particular genetic sequences is the result of multiple independent events instead of the dispersion of strains originated from a single event [43, 44]. However, once they emerge, the rapid spread of double-negative populations could be caused by the selection of these parasites by the pressure acting on these variants [45], as demonstrated also by stochastic simulation when the use of RDTs is based on the exclusive detection of the PfHRP2 antigen [46]. Despite the reason behind the emergence and spread of this genotypes in Central America, the presence of double-negative parasites in this endemic region has direct implications on the use of RDTs for routine diagnosis, especially in areas where microscopy is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Parasites with pfhrp2 and pfhrp3 gene (pfhrp2/3) deletions have emerged in regions of South America and since then, several studies have reported deletions in Africa and in India leading to false-negative RDT results (6)(7)(8). In some countries, a high proportion of RDT false negative results due to these gene deletions has led to the changes in diagnostic guidelines (9,10).…”
mentioning
confidence: 99%
“…The various nPCR methods used differ in limit of detection and this can cause type I and type II errors. Further, the pfhrp2 and pfhrp3 PCR assays do not reliably detect P. falciparum DNA derived from dried bloodspots (DBS) particularly at low parasite density (5,12), and gel-electrophoresis approaches do not detect deletions masked in polyclonal infections (6).…”
mentioning
confidence: 99%